Corneal bioengineering via electrospun nanofibers and nanoparticles - Salehi, Majid; Arabpour, Zohreh; Zamani, Sepehr; Alizadeh, Morteza; Gharibshahiyan, Maliheh; Rezvani, Milad; Aldaghi, Niloofar; Yekesadat, Seyed Meysam; R Djalilian, Ali (Journal of biomaterials applications, 2025)
Nanotechnology is transforming the area of corneal tissue engineering by improving scaffold design and enabling sophisticated therapeutic strategies. Nanomaterials are being used to improve the corneal scaffolds' mechanical strength, permeability, and transparency, as well as to enable the therapeutic agents' targeted delivery by nanocarriers. These improvements deal with important problems in corneal repair, like inflammation, infections, and neovascularization. While corneal transplantation remains a standard treatment, the risk of rejection and availability of donor tissue are the main limitations. Recent improvements in electrospinning have made it possible to make nanofibers that look like the natural extracellular matrix (ECM). These fibers have a large surface area and high porosity, which help cells grow, stick to each other, and change into different types of cells. Both synthetic and natural polymers have been successfully employed to fabricate biocompatible and biodegradable nanofibers, indicating their potential for the treatment of various corneal disorders. Electrospun nanofibers are very useful for corneal tissue engineering because they are easy to use, can be used in surgery, and are structurally similar to the cornea. Adding nanofibers and nanoparticles to corneal tissue engineering improves the scaffold and allows for targeted therapies, which means that there are more advanced ways to reconstruct and rehabilitate the cornea. This study investigates the application of naturally derived and synthetic nanoparticles in drug delivery systems and the development of composite nanoparticles, highlighting their potential to improve corneal tissue engineering techniques.